An anonymous eqestrian panegyric – an attempt to be excluded ”Wirydarz poetycki” from the collection of poems “Zbierana drużyna” - Kosmala, Paula (Melusine. Old Literature and Culture, 2024)
The article presents the poem Laudes konia from Andrew Lubieniecki’s sylva in comparison with O tymże alio modo from Jakub Teodor Trembecki’s Wirydarz poetycki. An attempt is made to determine the authorship of the work, as well as a biographical search. The work is also shown against the background of other hippie works of the period.